AgNPs@ZIF‐8 Hybrid Material‐Modified Polyethersulfone Microfiltration Membranes for Antibiofouling Property and Permeability Improvement. Issue 2 (17th December 2020) - Feng, Yue; Guo, Ning; Ren, Shaojie; Xie, Xuan; Xu, Juan; Wang, Yunkun
Abstract: Membrane fouling is a major hindrance to the effective application of polyethersulfone (PES) membranes. Synthetic silver nanoparticles @ zeolitic imidazolate framework‐8 (AgNPs@ZIF‐8) hybrid crystals were used to modify the PES microfiltration membranes for mitigating membrane fouling and better water permeability. The surface modification of AgNPs@ZIF‐8 hybrid crystals improved the antifouling property of the membranes. The number of live bacteria in the bacteria suspension was over 90 % less than that of control membranes. Furthermore, after surface modification, the membrane permeability was enhanced, which was due to increased surface hydrophilization of the membranes which could partly explain the improved antifouling property. The results demonstrate that the use of AgNPs@ZIF‐8 hybrid crystals is a feasible and attractive approach for the development of antifouling membranes. Abstract : The synthesis of silver nanoparticles @ zeolitic imidazolate framework‐8 (AgNPs@ZIF‐8) hybrid crystals and their further application as antibacterial agents for the control of fouling in polyethersulfone membranes is described. Experimental results prove that AgNPs@ZIF‐8 hybrid crystals could simultaneously and effectively improve the water permeability and antifouling property of these membranes.